2006
DOI: 10.1124/jpet.106.110346
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin and Oxaliplatin, but Not Carboplatin and Nedaplatin, Are Substrates for Human Organic Cation Transporters (SLC22A1–3 and Multidrug and Toxin Extrusion Family)

Abstract: We have examined the role of the human organic cation transporters [hOCTs and human novel organic cation transporter (hOCTN); SLC22A1-5] and apical multidrug and toxin extrusion (hMATE) in the cellular accumulation and cytotoxicity of platinum agents using the human embryonic kidney (HEK) 293 cells transiently transfected with the transporter cDNAs. Both the cytotoxicity and accumulation of cisplatin were enhanced by the expression of hOCT2 and weakly by hOCT1, and those of oxaliplatin were also enhanced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
241
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(257 citation statements)
references
References 20 publications
14
241
0
2
Order By: Relevance
“…For instance, oxaliplatin and cimetidine are substrates for both OCT1 and OCT3. [22][23][24][25] Our transport studies identify metformin as an OCT3 substrate (Fig. 4) with an affinity for OCT3 similar to that for OCT1 21,28,29 and a twofold higher maximal transport rate compared with OCT1.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, oxaliplatin and cimetidine are substrates for both OCT1 and OCT3. [22][23][24][25] Our transport studies identify metformin as an OCT3 substrate (Fig. 4) with an affinity for OCT3 similar to that for OCT1 21,28,29 and a twofold higher maximal transport rate compared with OCT1.…”
Section: Discussionmentioning
confidence: 93%
“…OCT1 substrates include antiviral drugs [18][19][20] and the antidiabetic drug metformin. 21 The anticancer drug oxaliplatin, 22,23 the histamine H 2 receptor antagonist cimetidine, 24,25 and the antiviral drug lamivudine 19,20 are substrates for both OCT1 and OCT3. Notably, hepatocytes are the pharmacological target cells of lamivudine, when it is used to treat chronic hepatitis B, 26 and of metformin.…”
mentioning
confidence: 99%
“…Unlike other platinum compounds, carboplatin is excreted mainly via glomerular filtration (Sorensen et al, 1992) and is not transported by organic cation transporters including hOCT1 and hOCT2 (Yonezawa et al, 2006). Moreover, a previous study reported that the accumulation of p-aminohippurate (a typical substrate of hOATs) was not inhibited by carboplatin in the experiment using rat renal cortical slices (Kanou et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…27,28 As there is little transport of cisplatin by MATE1 and MATE2-K, cisplatin is accumulated in the proximal tubular cells causing nephrotoxicity. A low-nephrotoxic platinum anticancer agent, oxaliplatin, was transported by OCT2 and MATE2-K, 27,28 suggesting that oxaliplatin does not accumulate in the renal proximal tubular cells. Therefore, loss of function of MATE2-K caused by cSNPs may lead to the accumulation of oxaliplatin in the kidney and the subsequent nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%